Electrical and structural properties of multi-walled carbon nanotube–doped polymer electrolyte for photo electrochemical device. (October 2018) - Sachdeva, A; Bhattacharya, B; Singh, Vijay; Singh, Abhimanyu; Tomar, SK; Singh, Pramod K
The present investigation deals with the preparation of multi-walled carbon nanotube (MWCNT)-doped plasticized polymer electrolyte. The nanocomposite has been prepared using solution casting method. Complex impedance spectroscopy study revealed the utmost room temperature conductivity of 5.6 × 10 −4 S/cm when optimized plasticized polymer electrolyte (poly(ethyl methacrylate)+30% sodium iodide+60% ethylene carbonate) was doped with 7% MWCNT. Temperature dependence of conductivity showed Arrhenius behavior. The surface morphology and crystalline–amorphous deviation of the composite was observed using scanning electron microscope. Perfect complexation of various components of the composite was confirmed from Fourier-transform infrared spectroscopy and X-ray diffraction (XRD) data. The transference number measurement was done to calculate the proportionate amount of ionic and electronic conductivity. A dye sensitized solar cell has been fabricated using maximum ionic conductivity of solid polymer electrolyte and its electrical parameters measured at 1 sun condition.